Breastfeeding and postpartum depression among women in urban field practice areas of Belagavi – A cross-sectional study - Bellad, Asha; Sivaji, Hemavathe; R, Sriram T; V N, Vignesh (Indian Journal of Community Health, 2025)
Introduction: Postpartum depression is an important medical issue and a common problem of women which also has a significant impact on the emotional and cognitive development of the baby. Studies in India have noted the prevalence of postnatal depression ranging between 11%-26.3%. Methodology: The present study was carried out among 506 postnatal women registered in two urban field practice areas of Belagavi. A pre-tested, standard, structured questionnaire was provided to them. After obtaining informed consent, the participants were asked to fill in the questionnaire. The collected data was entered and analyzed in SPSS Version 26. Results: Most women belonged to the age group 25-29 years (33.20%). Majority were Muslim by religion (62.45%) and housewife by occupation (66.60%). Most of them initiated breast feeding within 30 minutes to 4 hours, majority of them practiced exclusive breast feeding, around 70% of them faced some difficulty in breast feeding. Around 11.07% of the women had Edinburg Postnatal Depression Scale score ? 10. Edinburg Postnatal Depression Scale was found to be statistically significant with age, educational status, socio economic status, pregnancy planning, history of previous miscarriage/abortion, and difficulty in breast feeding. Conclusion: Many factors including breastfeeding is associated with postpartum depression. Early detection of mental health diseases is needed by training grassroot level staff with tools like Edinburgh scale to identify risk factors and integrating mental health activities into the routine antenatal care at primary level.